Study on green concrete (porous concrete) sustainability in order to support the sustainable construction in Indonesia - Laeli Fadloli; Hadi Susilo Arifin; Wonny Ahmad Ridwan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Currently implementation progress of green concrete (porous concrete0 is still very slow. The sustainable construction launched by the government has also not received a positive response from the construction sector. Greenery Open Spaces (RTH) and urban spatial planning in Indonesia have not accommodated the type of water-friendly pavement (porous concrete). Buildings that must meet the 30% of Green Base Cooeficient (KDH) also have not included the criteria for water-friendly concrete pavements. From the results of the Multi-Dimensional Scaling (MDS) analysis using Rapfish-R, it is known that the sustainability status of porous concrete is at a score of 71.9 (sufficiently sustainable). There is no leveraging factors from the ecological dimension. Leverage from economic dimensions, i.e.: added value for customer, durability and installation costs. Institutional dimensions, i.e.: application of ecolabels, product standards and criteria for RTH and KDH. Socio-technical dimension, i.e.: public understanding and perception, certification scheme, role of media, design and maintenance. From this leveraging factors, then can be formulized the strategy and roadmap for supporting the sustainable construction related to green concrete application